Staphylococcus arlettae mediated defense mechanisms and metabolite modulation against arsenic stress in Helianthus annuus - Qadir, Muhammad; Hussain, Anwar; Shah, Mohib; Hamayun, Muhammad; Iqbal, Amjad; Irshad, Muhammad; Ahmad, Ayaz; Alrefaei, Abdulwahed Fahad; Ali, Sajid (Frontiers in Plant Science, 2024)
Arsenate, a metalloid, acting as an analog to phosphate, has a tendency to accumulate more readily in plant species, leading to adverse effects. In the current study, sunflower seedlings were exposed to 25, 50 and 100 ppm of the arsenic. Likewise, a notable reduction (p<0.05) was observed in the relative growth rate (RGR) by 4-folds and net assimilation rate (NAR) by 75% of Helianthus annuus when subjected to arsenic (As) stress. Nevertheless, the presence of Staphylococcus arlettae, a plant growth-promoting rhizobacterium with As tolerance, yielded an escalation in the growth of H. annuus within As-contaminated media. S. arlettae facilitated the conversion of As into a form accessible to plants, thereby, increasing its uptake and subsequent accumulation in plant tissues. S. arlettae encouraged the enzymatic antioxidant systems (Superoxide dismutase (SOD), peroxidase (POD), ascorbate peroxidase (APX) and catalase (CAT)) and non-enzymatic antioxidants (flavonoids, phenolics, and glutathione) in H. annuus seedlings following substantial As accumulation. The strain also induced the host plant to produce osmolytes like proline and sugars, mitigating water loss and maintaining cellular osmotic balance under As-induced stress. S. arlettae rectified imbalances in lignin content, reduced high malonaldehyde (MDA) levels, and minimized electrolyte leakage, thus counteracting the toxic impacts of the metal. Furthermore, the strain exhibited the capability to concurrently encourage plant growth and remediate As-contaminated growth media through 2-folds rate of biotransformation and bio-mobilization.